Modern Applications of Electronic Nose: A Review - Hasin Alam; S. Hasan Saeed (International Journal of Electrical and Computer Engineering (IJECE), 2013)
Electronic noses have provided a plethora of benefits to a variety of commercial industries, including the agricultural, biomedical, cosmetics, environmental, food, manufacturing, military, pharmaceutical, regulatory, and various scientific research fields. Advances have improved product attributes, uniformity, and consistency as a result of increases in quality control capabilities afforded by electronic-nose monitoring of all phases of industrial manufacturing processes. This paper is a review of some of the more important and modern applications that have been of greatest benefit to the humankind.DOI:http://dx.doi.org/10.11591/ijece.v3i1.1226